2018
DOI: 10.12944/crnfsj.6.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Properties and Cytotoxic Activity Against Colon Cancer Cell WiDr of Rhizopus Oryzae and Rhizopus Oligosporus-Fermented Black Rice Bran Extract

Abstract: Black rice bran (BRB) was reported to have several bioactive compounds which can potentially as antioxidant and reduce the colon cancer incidence. Fermentation was reported to be able to increase bioavailability through deliberating the bioactive compounds from the cellular matrix. The aim of this study was to improve the bioavailability of BRB bioactive compounds which offer beneficial health properties as antiproliferative against colon cancer cell WiDr and confer antioxidant activity by fermentation. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
2
11
0
1
Order By: Relevance
“…In addition, the antioxidative and antiproliferative activities of FBRB extract were also higher than those of nonfermented BRB [54]. The antioxidative activity of BRB is mainly influenced by phenolic acids bound to cell wall polysaccharides, and thus the lignocellulolytic activity of fungi may elevate the level and activity of free phenolics [54]. These findings confirm that fermentation is a critical method for the enhancement of chemopreventive components in rice.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…In addition, the antioxidative and antiproliferative activities of FBRB extract were also higher than those of nonfermented BRB [54]. The antioxidative activity of BRB is mainly influenced by phenolic acids bound to cell wall polysaccharides, and thus the lignocellulolytic activity of fungi may elevate the level and activity of free phenolics [54]. These findings confirm that fermentation is a critical method for the enhancement of chemopreventive components in rice.…”
Section: Discussionmentioning
confidence: 86%
“…The above authors suggested that FBRA extract may contain a variety of bioactive oligopeptides, which are toxic to cancer cells [18]. Black rice bran (BRB) has been fermented by Rhizopus oryzae and/or Rhizopus oligosporus to produce fermented BRB (FBRB) [54]. The ethanol and methanol extracts of FBRB had higher total polyphenol content (TPC) compared with nonfermented BRB [54].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analisis profil gelatinisasi dilakukan berdasarkan metode Nindita et al (2018) menggunakan rapid visco analyzer (RVA-4500, Swedia). Analisis komponen antioksidan dilakukan terhadap filtrat sampel yang didapat dari hasil ekstraksi TKHA berdasarkan metode Zulfafamy et al (2018). Komponen antioksidan yang dianalisis yaitu total senyawa fenolik (Chen et al, 2015), total antosianin (Sutharut dan Sudarat, 2012) dan kapasitas antioksidan berdasarkan metode 2,2-Diphenyl-1-Picrylhydrazyl (DPPH) (Bobo-García et al, 2015) dan ferric reducing antioxidant power (FRAP) (Zahin et al, 2013).…”
Section: Karakterisasi Tkhaunclassified